Differential effects of attentional focus strategies during long-term resistance training - Schoenfeld, B. J.; Vigotsky, A.; Contreras, B.; Golden, S.; Alto, A.; Larson, R.; Winkelman, N.; Paoli, A. (European Journal of Sport Science, 2018)
The purpose of this study was to investigate the effects of using an internal versus external focus of attention during resistance training on muscular adaptations. Thirty untrained college-aged men were randomly assigned to an internal focus group (INTERNAL) that focused on contracting the target muscle during training (n= 15) or an external focus group (EXTERNAL) that focused on the outcome of the lift (n= 15). Training for both routines consisted of 3 weekly sessions performed on non-consecutive days for 8 weeks. Subjects performed 4 sets of 8-12 repetitions per exercise. Changes in strength were assessed by six repetition maximum in the biceps curl and isometric maximal voluntary contraction in knee extension and elbow flexion. Changes in muscle thickness for the elbow flexors and quadriceps were assessed by ultrasound. Results show significantly greater increases in elbow flexor thickness in INTERNAL versus EXTERNAL(12.4% vs. 6.9%, respectively); similar changes were noted in quadriceps thickness. Isometric elbow flexion strength was greater for INTERNAL while isometric knee extension strength was greater for EXTERNAL, although neither reached statistical significance. The findings lend support to the use of a mind-muscle connection to enhance muscle hypertrophy.